Intensity- and timing-dependent modulation of motion perception with transcranial magnetic stimulation of visual cortex. (October 2020) - Gamboa Arana, Olga Lucia; Palmer, Hannah; Dannhauer, Moritz; Hile, Connor; Liu, Sicong; Hamdan, Rena; Brito, Alexandra; Cabeza, Roberto; Davis, Simon W.; Peterchev, Angel V.; Sommer, Marc A.; Appelbaum, Lawrence G.
Abstract: Despite the widespread use of transcranial magnetic stimulation (TMS) in research and clinical care, the dose–response relations and neurophysiological correlates of modulatory effects remain relatively unexplored. To fill this gap, we studied modulation of visual processing as a function of TMS parameters. Our approach combined electroencephalography (EEG) with application of single pulse TMS to visual cortex as participants performed a motion perception task. During each participants' first visit, motion coherence thresholds, 64-channel visual evoked potentials (VEPs), and TMS resting motor thresholds (RMT) were measured. In second and third visits, single pulse TMS was delivered at one of two latencies, either 30 ms before the onset of motion or at the onset latency of the N2 VEP component derived from the first session. TMS was delivered at 0%, 80%, 100%, or 120% of RMT over the site of N2 peak activity, or at 120% over vertex. Behavioral results demonstrated a significant main effect of TMS timing on accuracy, with better performance when TMS was applied at the N2-Onset timing versus Pre-Onset, as well as a significant interaction, indicating that 80% intensity produced higher accuracy than other conditions at the N2-Onset. TMS effects on the P3 VEP showed reduced amplitudes in the 80% Pre-Onset condition, an increase for the 120% N2-Onset condition, and monotonic amplitude scaling with stimulation intensity. The N2 component was not affected by TMS. These findings reveal the influence of TMS intensity and timing on visual perception and electrophysiological responses, with optimal facilitation at stimulation intensities below RMT. Highlights: Studied modulation of visual perception and EEG due to single-pulse TMS. Delivered spTMS at two latencies and five intensities to either visual cortex or vertex. Found a significant effect of timing and an interaction with intensity on accuracy. P3 VEP showed monotonic amplitude scaling with stimulation intensity. Findings generally indicate facilitation at stimulation intensities below RMT.